Genomic Characterization of Prevalent mcr-1, mcr-4, and mcr-5 Escherichia coli Within Swine Enteric Colibacillosis in Spain - García-Meniño, Isidro; Díaz-Jiménez, Dafne; García, Vanesa; de Toro, María; Flament-Simon, Saskia C.; Blanco, Jorge; Mora, Azucena (Frontiers in Microbiology, 2019)
Antimicrobial agents are crucial for the treatment of many bacterial diseases in pigs, however, the massive use of critically important antibiotics such as colistin, fluoroquinolones and 3rd-4th-generation cephalosporins often selects for co-resistance. Based on a comprehensive characterization of 35 colistin-resistant Escherichia coli from swine enteric colibacillosis, belonging to prevalent Spanish lineages, the aims of the present study were to investigate the characteristics of E. coli clones successfully spread in swine and to assess the correlation of the in vitro results with in silico predictions from WGS data. The resistome analysis showed six different mcr variants: mcr-1.1; mcr-1.10; mcr-4.1; mcr-4.2; mcr-4.5 and mcr-5.1. Additionally, blaCTX-M-14, blaCTX-M-32 and blaSHV-12 genes were present in seven genomes. PlasmidFinder revealed that mcr-1.1 genes located mainly on IncHI2 and IncX4 types, and mcr-4 on ColE10-like plasmids. Twenty-eight genomes showed a gyrA S83L substitution, and 12 of those 28 harboured double-serine mutations gyrA S83L and parC S80I, correlating with in vitro quinolone-resistances. Notably, 16 of the 35 mcr-bearing genomes showed mutations in the PmrA (S39I) and PmrB (V161G) proteins. The summative presence of mechanisms, associated with high-level of resistance to quinolones/fluoroquinolones and colistin, could be conferring adaptive advantages to prevalent pig E. coli lineages, such as the ST10-A (CH11-24), as presumed for ST131. SerotypeFinder allowed the H-antigen identification of in vitro non-mobile (HNM) isolates, revealing that 15 of the 21 HNM E. coli analyzed were H39. Since the H39 is associated with the most prevalent O antigens worldwide within swine colibacillosis, such as O108 and O157, it would be probably playing a role in porcine colibacillosis to be considered as a valuable subunit antigen in the formulation of a broadly protective Enterotoxigenic E. coli (ETEC) vaccine. Our data show common features with other European countries in relation to a prevalent clonal group (CC10), serotypes (O108:H39, O138:H10, O139:H1, O141:H4), high plasmid content within the isolates and mcr location, which would support global alternatives to the use of antibiotics in pigs. Here, we report for first time a rare finding so far, which is the co-occurrence of double colistin-resistance mechanisms in a significant number of E. coli isolates.